IMF Survey, Volume 33, Issue 19. (IMF Survey; IMF Survey ;, 2004)
To help Iraq stabilize its economy and restructure its massive debt, the IMF in late September approved USD 436.3 million in Emergency Post-Conflict Assistance. This financing lends support to prudent monetary and fiscal policies and is designed to bolster institutional capacity and potentially lay the basis for a more ambitious economic program later next year. Two senior staff in the IMF's Middle East and Central Asia Department-Lorenzo Perez, Senior Advisor, and Adam Bennett, Division Chief-talk with Sheila Meehan of the IMF Survey about Iraq's economic prospects and the IMF's recently released staff report.